The Ritual of Ecolexicon in the Text of Batar in Tetun Fehan Malaka,Timor, East Nusa Tenggara Province: Ecolinguistic View - Magdalena Namok nahak, Maria (e-Journal of Linguistics; Vol 14 No 1 (2020): e-jl January, 2020)
This paper entitled "The Ritual of Ecolexicon in the Text of Batar in Tetun Fehan Malaka East Nusa Tenggara Province: Ecolinguistic view is a part of the corpus of local wisdom that needs to be examined for the sake of sustainability of eternity ecology of batar. This research aims to analyze and discover the ritual process in text of batar by applying the theory of ecolinguistic focusing on three logical dimensions (ideological, biological, and sociological); that supported the theory of linguistic and cultural linguistic theory. The approach used in this research is descriptive qualitative with quantitative naturalistic in nature. This research applies fieldwork methods. The form of research uses the method of participation observation, interviews, and triangulations. The text of batar is rich of noun, categorical, verb, adjective, and numeral lexicons. The implementation of the four dimensions of modification gave birth to a totality in dissecting the financial ecolexicon in interdependence with the inner rituals, namely ideological dimensions, biological dimensions, sociological dimensions and textual dimensions. K eywords: Batar Text, Lexicon, Ritual, Tetun Fehan